Redistribution of reactive odd nitrogen in the lower arctic stratosphere - Huebler, G.; Fahey, D. W.; Kelly, K. K.; Montzka, D. D.; Carroll, M. A.; Tuck, A. F.; Heidt, L. E.; Pollock, W. H.; Gregory, G. L.; Vedder, J. F. (1990)
In-situ measurements of total reactive odd nitrogen NO(y), were made from the NASA DC-8 aircraft in the lower arctic stratosphere during the 1989 Airborne Arctic Stratospheric Expedition. Throughout January and February, NO(y) mixing ratios were typically between 0.5 and 3 parts per billion by volume (ppbv) at altitudes between 10 and 12.5 km. During several flights late in the mission, events of unusually light NO(y) occurred with mixing ratios up to 12 ppbv at these altitudes. Simultaneous measurements of N2O, O3, and H2O during these events suggest that large changes in NO(y) are not expected. The elevated NO(y) values are interpreted as a vertical redistribution of NO(y) in the lower stratosphere resulting from gravitational sedimentation of aerosol particles containing HNO3. No evidence of the redistribution of H2O is noted, consistent with observations of denitrification without dehydration higher in the stratosphere.